Use of mass spectrometry-based lipidomics to probe PITPα (phosphatidylinositol transfer protein α) function inside the nuclei of PITPα+/+ and PITPα−/− cells. (26th October 2004) - Hunt, A.N.; Alb, J.G.; Koster, G.; Postle, A.D.; Bankaitis, V.A.
Abstract : The mammalian phospholipid exchange protein PITPα (phosphatidylinositol transfer protein alpha), found in both extranuclear and endonuclear compartments, is thought in part to facilitate nuclear import of the PtdIns (phosphatidylinositol) consumed in the generation of proliferation-associated endonuclear diacylglycerol accumulations. Unlike phosphatidylcholine, endonuclear PtdIns is not synthesized in situ . However, despite progressive postnatal lethality of PITPα ablation in mice, PITPα −/− MEF (mouse embryonic fibroblasts) lack an obviously impaired proliferative capacity. We used ESI-MS (tandem electrospray ionization-MS) to monitor incorporation of the deuterated phospholipid precursors, choline- d 9 and inositol- d 6, into molecular species of whole cell and endonuclear phosphatidylcholine and PtdIns over 24 h to assess the contribution of PITPα to the nuclear import of PtdIns into MEF cells. In cells labelled for 1, 3, 6, 12 and 24 h fractional inositol- d 6 incorporation into whole-cell PtdIns species was consistently higher in PITPα −/− MEF implying greater flux through its biosynthetic pathway. Moreover, endonuclear accumulation of PtdIns- d 6 was apparent in the PITPα −/− cells and mirrored that in PITPα +/+ cells. Together, these results suggest that the essential endonuclear PtdIns import via PITPα can be accommodated by other mechanisms.